Struktur Komunitas Vegetasi Bawah Pada Perkebunan Kelapa Sawit (Elaeis guineensis Jacq) di Kecamatan Kampar Kiri Tengah Kabupaten Kampar Sebagai Rancangan Media Poster Pada Pembelajaran Biologi SMA - Lili Nur Indahsari; Fitra Suzanti; Suwondo Suwondo (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aimed to analyze the structure of understory vegetation communities in oil palm plantations located in Kampar Kiri Tengah District, Kampar Regency. The research was conducted in March 2025 using a survey method. Sampling was carried out through purposive random sampling by considering oil palm age. Parameters observed included species composition, density, frequency, importance value index, diversity index, similarity index, and dominance index. Physical chemical environmental factors measured comprised soil temperature, air temperature, soil pH, and light intensity. Results showed that understory vegetation consisted of 31 species from 18 families, with a total of 3580 individuals recorded. The highest density was found in Cyperus kyllingia from the Cyperaceae family with a relative density of 37.23 percent, while the lowest density occurred in Mikania micrantha from the Asteraceae family at 0.08 percent. The highest relative frequency was observed in Cyperus rotundus at 4.84 percent, whereas the lowest was recorded for Davallia tasmanii at 2.13 percent. The highest importance value index was recorded for Cyperus kyllingia at 42.97 percent, while the lowest was found in Lindsaea cultrata at 0.24 percent. The diversity index was categorized as moderate. The evenness index ranged from 0.61 to 0.69, indicating moderate uniformity. The dominance index showed no species dominated excessively. Research findings were integrated into poster-based learning media and validated by experts as very valid. This study demonstrates strong potential for using understory vegetation community structure as learning media for ecosystem component topics.